Targeting Ataxia telangiectasia mutated (ATM) and DNA dependent protein kinase catalytic subunit (DNA-PKcs) for synthetic lethality application in breast cancer - Albarakati, Nada (2015)
BRCA1 germ-line mutations predispose to hereditary breast and ovarian cancers. Cells lacking functional BRCA1 protein are deficient in the homologous recombination DNA repair pathway. Base excision repair (BER) is essential for processing base damage induced by endogenous and exogenous sources. Recently, BRCA1 was shown to transcriptionally regulate expression of genes involved in BER. The primary aim of the work described in this thesis was to investigate whether targeting the double-strand break pathway in BRCA1-BER deficient cells using ATM or DNA-PKcs inhibitors would be synthetically lethal.